The relationship between depression and academic burnout among undergraduate students majoring in eldercare services: a moderated mediation model - Lin, Yingjie; Pan, Siyu; He, Jianyao; Cheng, Qi; Wei, Hongmin; Zhao, Li (Frontiers in Psychology, 2025)
ObjectivesTo explore the relationship between depression, self-efficacy, academic burnout, and social support among undergraduate students majoring in eldercare services in China.MethodsA cross-sectional study was carried out among 957 students majoring in eldercare services across four provinces of China. The study employed questionnaires based on the Center for Epidemiological Studies Depression Scale, General Self-Efficacy Scale, Learning Burnout Scale, and Perceived Social Support Scale. Using SPSS 22.0 for descriptive analysis and Pearson correlation analysis, and constructed a moderated mediation model using PROCESS.ResultsThe findings reveal that 26.92% of students suffer from academic burnout. Depression is significantly negatively correlated with self-efficacy, positively correlated with academic burnout. Self-efficacy is negatively correlated with academic burnout. The results of the moderated mediation model showed that the mediating effect value of self-efficacy on depression and academic burnout was 0.139, accounting for 19.02% of the total effect. The interaction term between depression and social support has a negative effect on self-efficacy β = −0.203, and a positive effect on academic burnout β = 0.106.ConclusionThere is a positive correlation between depression and academic burnout among undergraduate students majoring in eldercare services. Self-efficacy partially mediates the relationship between depression and academic burnout, while social support plays a moderating role.